2011
DOI: 10.1186/1471-2202-12-40
|View full text |Cite
|
Sign up to set email alerts
|

The role of shear stress in Blood-Brain Barrier endothelial physiology

Abstract: BackgroundOne of the most important and often neglected physiological stimuli contributing to the differentiation of vascular endothelial cells (ECs) into a blood-brain barrier (BBB) phenotype is shear stress (SS). With the use of a well established humanized dynamic in vitro BBB model and cDNA microarrays, we have profiled the effect of SS in the induction/suppression of ECs genes and related functions.ResultsSpecifically, we found a significant upregulation of tight and adherens junctions proteins and genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
339
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(348 citation statements)
references
References 49 publications
7
339
2
Order By: Relevance
“…P-glycoprotein, a member of the ABC superfamily, is encoded by the MDR l gene and has been demonstrated to act as a very efficient toxin efflux molecule and to confer resistance to a wide range of insults (21). Previous studies have shown that LSS could induce the endothelial expression of drug transporters and metabolic properties that allow the blood-brain barrier to shield the central nerve system from potentially harmful substances (22). The LSSinduced MDR1 and other exporters (such as ABCB4, ABCD2, and ABCG2) (23,24), together with other metabolizing enzymes (such as CYP1B1, CYP24A1, CYP27A1, and SULT1A1), may orchestrate a multistep detoxification program composed of metabolization and efflux.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein, a member of the ABC superfamily, is encoded by the MDR l gene and has been demonstrated to act as a very efficient toxin efflux molecule and to confer resistance to a wide range of insults (21). Previous studies have shown that LSS could induce the endothelial expression of drug transporters and metabolic properties that allow the blood-brain barrier to shield the central nerve system from potentially harmful substances (22). The LSSinduced MDR1 and other exporters (such as ABCB4, ABCD2, and ABCG2) (23,24), together with other metabolizing enzymes (such as CYP1B1, CYP24A1, CYP27A1, and SULT1A1), may orchestrate a multistep detoxification program composed of metabolization and efflux.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB ECs are also characterized by very high density of mitochondria denoting high metabolic activity (23) to support all the specialized cellular activities bestowed upon these highly specialized cells. In addition, previous work from our group has shown that blood flow can modulate the bioenergetic behavior of the BBB endothelial cells favoring the expression of the key metabolic enzyme pyruvate dehydrogenase (switch controller from anaerobic to aerobic pathway) (19). Contrarily, the RNA level of lactate dehydrogenase (switch controller from aerobic to anaerobic pathway) showed decreased expression.…”
Section: Structural and Functional Complexity Of Blood Brain Barrier mentioning
confidence: 93%
“…Topographic membrane localization of these transporters is indicative of the polarity of the endothelial functions and differentiation that sets apart the BBB endothelium from other vascular beds. The BBB endothelial cytoplasm is richly endowed with enzymes(18) including adenosine triphosphatase, acid and alkaline phosphatases, Na + /K + /ATPase, monoamine oxidase, cytochrome p450s and various dehydrogenases (19)(20)(21)(22). The BBB ECs are also characterized by very high density of mitochondria denoting high metabolic activity (23) to support all the specialized cellular activities bestowed upon these highly specialized cells.…”
Section: Structural and Functional Complexity Of Blood Brain Barrier mentioning
confidence: 99%
“…A pulsatile flow was imposed to better mimic the fluid dynamic conditions in vivo. It was shown that ECs exposed to shear stress and fluid pressure had a comparable morphology and functionality with respect to their in vivo counterparts (56,57). Thus, DIV-BBB models may be used to further investigate in vitro the immune cell trafficking across the BBB (Tab.…”
Section: The Blood Brain Barriermentioning
confidence: 99%
“…For example, to study the physiological and functional behavior of distinct segments of the human cerebrovascular network, a novel capillary-venule modular system composed of a combination of 2 DIV-BBBs was presented (56,57). Both the venule and the capillary module were configured as cHFBs.…”
Section: The Blood Brain Barriermentioning
confidence: 99%